2012
DOI: 10.1128/aem.01046-12
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Systematic Study To Assess Norovirus Contamination in Oysters from Commercial Harvesting Areas in the United Kingdom

Abstract: The contamination of bivalve shellfish with norovirus from human fecal sources is recognized as an important human health risk. Standardized quantitative methods for the detection of norovirus in molluscan shellfish are now available, and viral standards are being considered in the European Union and internationally. This 2-year systematic study aimed to investigate the impact of the application of these methods to the monitoring of norovirus contamination in oyster production areas in the United Kingdom. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 34 publications
11
88
2
Order By: Relevance
“…Several studies have documented higher prevalences and levels of both NoV GI and NoV GII in commercially harvested shellfish during the winter (102,103,104,105,106,107), although some studies have reported no substantial summer-winter seasonality with respect to the prevalence of these genogroups in shellfish (108) and shellfish-growing waters (109). This discrepancy could be due to high fluxes of sewage contamination throughout the year in the latter study sites.…”
Section: Seasonal and Environmental Influencesmentioning
confidence: 45%
See 1 more Smart Citation
“…Several studies have documented higher prevalences and levels of both NoV GI and NoV GII in commercially harvested shellfish during the winter (102,103,104,105,106,107), although some studies have reported no substantial summer-winter seasonality with respect to the prevalence of these genogroups in shellfish (108) and shellfish-growing waters (109). This discrepancy could be due to high fluxes of sewage contamination throughout the year in the latter study sites.…”
Section: Seasonal and Environmental Influencesmentioning
confidence: 45%
“…In the United Kingdom, average levels of NoV in Pacific oysters (Crassostrea gigas) during winter months (October to March) may be as much as 17 times higher than those during the remainder of the year (110). This seasonal pattern has been observed to mirror variations in water temperature (104) and in salinity and rainfall (103). Richards et al showed that long-term (120-day) frozen conditions do not decrease NoV RNA titers and that repeated freezing and thawing do not inactivate NoV in the environment (111).…”
Section: Seasonal and Environmental Influencesmentioning
confidence: 99%
“…The observed prevalence ranged from 3.9 to 76.2% in shellfish (14,28,29), 6.7 to 55.5% in fresh produce (30), and 15.1 to 45% in drinking water sources and surface water (31,32). These positive NoV signals may induce recalls or rejections of food batches associated with NoV contamination, causing economic loss in international markets.…”
Section: Discussionmentioning
confidence: 99%
“…Fruits, vegetables, and shellfish pose a significant risk for disease transmission because they are consumed raw and may be subject to norovirus contamination from water sources. Norovirus has been recovered from a variety of food products ranging from oysters to romaine lettuce, raspberries, and other produce (119)(120)(121)(122)(123)(124)(125). Additionally, the use of contaminated water for reconstituting food products has been implicated in widespread outbreaks (e.g., custard in Bristol, United Kingdom) (126).…”
Section: Food Restaurants and Cateringmentioning
confidence: 99%